A retrospective chart review to assess the impact of alpha-guided transcranial magnetic stimulation on symptoms of PTSD and depression in active-duty special operations service members - Bailar-Heath, Marybeth; Burke, Riley; Thomas, Delisha; Morrow, Chad D. (Frontiers in Psychiatry, 2024)
Introduction: Special Operations Forces service members (SOF) are regularly exposed to traumatic and concussive events, increasing the prevalence of symptoms of post-traumatic stress disorder (PTSD) and depression, shortening potential years of service.Methods: This retrospective chart review presents preliminary data on a Human Performance Optimization (HPO) program that provided an average of 30 sessions of individualized alpha frequency repetitive transcranial magnetic stimulation (α-rTMS) to active-duty SOF as to reduce symptoms of PTSD and depression following traumatic brain injury. Scores from the PTSD Checklist for DSM-5, PROMIS Depression short form and Perceived Deficits Questionnaire (PDQ) were reviewed.Results: Significant reductions were noted after the HPO program in all clinical scales with an average 37% decrease in PCL-5 (p<.01), 11.3% reduction in PROMIS depression T-scores (p<.01), and 45.5% reduction in PDQ scales by session 30 (p<.01), with side effects matching those commonly reported in rTMS. Additionally, the average PCL-5 score decreased from 42.9 to 27 by end of the treatment program, below the clinical threshold of 33 for presence of PTSD.Conclusion: This data provides preliminary support for safe application of α-rTMS for symptom reduction in active-duty special operations military personnel.